2016
DOI: 10.17269/cjph.107.5344
|View full text |Cite
|
Sign up to set email alerts
|

Retail food environments research in Canada: A scoping review

Abstract: OBJECTIVES: The field of retail food environments research is relatively new in Canada. The objective of this scoping review is to provide an overview of retail food environments research conducted before July 2015 in Canada. Specifically, this review describes research foci and key findings, identifies knowledge gaps and suggests future directions for research. METHODS:A search of published literature concerning Canadian investigations of retail food environment settings (food stores, restaurants) was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 64 publications
3
96
1
7
Order By: Relevance
“…The aim of the workshop was to introduce citizens and other key stakeholders to retail food environments, and increase their involvement in considering as a community how where we live, work and play influences our food choice opportunities. 11 The Office of Public Engagement at Memorial University runs an annual event series called Engage Memorial, a knowledge mobilization initiative intended to support researchers in showcasing collaboration between the university and the community, and to build capacity for public engagement. Engage Memorial presented an opportunity for us to augment our existing HCSNL knowledge exchange plan with The Food In This Place.…”
Section: The Food In This Placementioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the workshop was to introduce citizens and other key stakeholders to retail food environments, and increase their involvement in considering as a community how where we live, work and play influences our food choice opportunities. 11 The Office of Public Engagement at Memorial University runs an annual event series called Engage Memorial, a knowledge mobilization initiative intended to support researchers in showcasing collaboration between the university and the community, and to build capacity for public engagement. Engage Memorial presented an opportunity for us to augment our existing HCSNL knowledge exchange plan with The Food In This Place.…”
Section: The Food In This Placementioning
confidence: 99%
“…The retail food environment, including the availability, accessibility and affordability of food in retail settings, has emerged as an important contributor to population health and dietary behaviours. 11 We will speak to how citizen science concepts and methods demonstrate how everyday exposures in the retail food environment can be highlighted as a contributor to health.…”
mentioning
confidence: 99%
“…As Minaker et al found in this special issue, most of the Canadian research has been published in the last 5 years. 1 The field is growing and dynamic.…”
Section: Resultsmentioning
confidence: 99%
“…As Minaker et al point out, retail food environments research has expanded rapidly in Canada, only one paper having been published before 2005 and 66 between 2010 and 2015. 1 The increase in publications is a reflection of a concerted effort from researchers across Canada, but is not unique to Canada. 2 This special supplement covers a wide range of methodological approaches, populations and geographic foci.…”
mentioning
confidence: 99%
“…1 Significantly, conflating the provincial Norths and Far North (the Northwest Territories, the Yukon, and Nunavut) fails to capture the unique contexts and challenges that characterize food retailing in these locales. An in-depth examination of the retail environment in the provincial North reveals Grassroots Indigenous movements and organizations responding to the changes in the subsidy program have brought the extremely high rates of food insecurity in the Canadian North to the attention of the broader Canadian public through social media campaigns and on Facebook pages such as Feeding My Family.…”
Section: Introductionmentioning
confidence: 99%